Eponyms in dermatology literature linked to Otorhinolaryngology - Ahed Aqeel; Khalid Al Aboud; Ashraf Al Harbi; Adnan Alehibi; Rasha Al Harbi (Our Dermatology Online, 2017)
In some disorders, there are symptoms or signs shared by dermatology and ears, nose and throat (ENT) specialty. It is also known that there are eponyms in dermatology and ENT. The aim in this short communication is to shed some lights on the eponyms in dermatology literature linked to ENT.